Laparoscopic Common Bile Duct Exploration: 9 Years Experience from a Single Center - Darkahi, Bahman; Liljeholm, Håkan; Sandblom, Gabriel (Frontiers in Surgery, 2016)
Abstract INTRODUCTION The aim of the study was to evaluate the safety and feasibility of laparoscopic common bile duct exploration (LCBDE) through cholangiotomy with T-tube placement in one séance for common bile duct stones (CBDS). METHODS Between January 2005 and December 2010, a total of 99 patients with CBDS stones undergoing LCBDE with T-tube insertion at Enköping Hospital, Sweden, were registered prospectively. All patients were followed up by review of the patient records according to a standardised protocol. RESULTS No severe intraoperative complications were registered. Four procedures required conversion to open cholecystectomy due to impacted stones or technical difficulty. The mean operative time was 194 minutes (standard deviation [SD] 57 minutes). The mean postoperative hospital stay was 4.8 days, SD 2.4 days. At secondary cholangiography, 2 (2%) retained stones were found. Two (2%) patients had minor bile leakage, which resolved spontaneously. None of the patients experienced biliary peritonitis, biliary fistula, pancreatitis, or cholangitis. No death within thirty days after surgery was seen. No patient was readmitted with clinical signs of stricture. CONCLUSION If performed by a surgeon familiar with the technique, LCBDE is a safe and feasible alternative for managing CBDS. The advantages are most pronounced in the case of multiple and large CBDS. The risk for retained stones and stricture is low.